2017
DOI: 10.1016/j.jnutbio.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Diet-dependent retinoid effects on liver gene expression include stellate and inflammation markers and parallel effects of the nuclear repressor Shp

Abstract: For mice, a maternal vitamin A (VA) deficient diet initiated from mid-gestation (GVAD) produces serum retinol deficiency in mature offspring. We hypothesize that the effects of GVAD arise from pre-weaning developmental changes. We compare the effect of this GVAD protocol in combination with a post-weaning high fat diet (HFD) or high carbohydrate diet (LF12). Each is compared to an equivalent VA sufficient combination. GVAD extensively decreased serum retinol and liver retinol, retinyl esters, and retinoid home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…These genes are mostly inflammation markers that are also suppressed by deletion of Shp/Nr0b2 (Kim et al, 2014) (Supplementary Figure 1). We have shown that the response changes in Cyp1b1−/− mice compared to WT mice correlate remarkably with the changes reported in Shp−/− mice (Maguire et al, 2017). Shp redirects postprandial metabolism from glycogen synthesis to glycolysis and lipogenesis (Garruti et al, 2012) (Figure 5B).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…These genes are mostly inflammation markers that are also suppressed by deletion of Shp/Nr0b2 (Kim et al, 2014) (Supplementary Figure 1). We have shown that the response changes in Cyp1b1−/− mice compared to WT mice correlate remarkably with the changes reported in Shp−/− mice (Maguire et al, 2017). Shp redirects postprandial metabolism from glycogen synthesis to glycolysis and lipogenesis (Garruti et al, 2012) (Figure 5B).…”
Section: Discussionsupporting
confidence: 80%
“…This basal diet (LF12) is similar to the low fat, post-weaning, control diet (LFD), sharing 20 percent refined protein content and approximately 70 percent kcal from carbohydrate (Supplementary Table 1). The combination of LF12 maternal diet with the HFD post-weaning (LF12-HFD) produced few liver gene expression differences when compared to the standard breeder diet combination (BD-HFD) (Maguire et al, 2017). Nevertheless, body weight and adipose were significantly decreased (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytochrome P450 1b1 (Cyp1b1) has a major influence on obesity and genes that have been linked to Type 2 diabetes [1][2][3]. Such changes may be initiated during pregnancy [4,5]. Cyp1b1 exhibits diverse expression in mouse embryo mesenchymal progenitor cells [6][7][8] and vascular cells [9,10].…”
Section: Introductionmentioning
confidence: 99%